2008
DOI: 10.1089/gte.2008.0014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the CTNS Gene in Nephropathic Cystinosis Mexican Patients: Report of Four Novel Mutations and Identification of a False Positive 57-kb Deletion Genotype with LDM-2/Exon 4 Multiplex PCR Assay

Abstract: Our sample of Mexican patients display allelic heterogeneity as compared to European or North American cystinosis cases. The identification of novel mutations might suggest the presence of exclusive American CTNS alleles in Mexican population. In order to prevent the false positive assignation of 57-kb deletion genotype, as caused by the presence of another type of intragenic CTNS gross deletion, we propose to analyze a different control CTNS exon to those originally reported in both LDM multiplex PCR assays, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
(39 reference statements)
2
15
0
1
Order By: Relevance
“…The intronic splice site mutation (IVS3+5g>t) detected in patient 2 led to the skipping of exon 3 after RT-PCR/ sequencing analysis as the similar splicing mutation at the same position (IVS3+5g>a), which was also demonstrated to lead to exon 3 skipping in a Mexican patient with nephropathic cystinosis (AlcÄntara-Ortigoza et al 2008), confirming the importance of the guanine base at the IVS+5 position for CTNS exon 3 transcription.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The intronic splice site mutation (IVS3+5g>t) detected in patient 2 led to the skipping of exon 3 after RT-PCR/ sequencing analysis as the similar splicing mutation at the same position (IVS3+5g>a), which was also demonstrated to lead to exon 3 skipping in a Mexican patient with nephropathic cystinosis (AlcÄntara-Ortigoza et al 2008), confirming the importance of the guanine base at the IVS+5 position for CTNS exon 3 transcription.…”
Section: Discussionsupporting
confidence: 53%
“…A single study in the Far East (Thailand) also reported the absence of the 57-kb mutant allele in six patients of Thai and Cambodian origins (Yeetong et al 2012). Apparently, this common mutation is restricted to the Northern European/American populations and, to a lesser extent, to countries of possible genetic contact as in Italy (Mason et al 2003) and Mexico (AlcÄntara-Ortigoza et al 2008). This supports the theory that this founder mutation originated very recently during human evolution, perhaps less than 2,000 years ago somewhere in Northern Europe (Kalatzis and Antignac 2002); so it has not got the chance to spread to remote ethnicities.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Still, large geographic regions, such as sub-Saharan Africa, South-East Asia and the Far East are underrepresented in the genetic spectrum of their cystinosis patients. Although accurate statistics are lacking in the developing world [21], recent studies from the Middle East [17][18][19][20], Mexico [22] and South Africa [23] may indicate that the incidence of cystinosis in many of these countries is expected to be higher than that of Europe and North America. Moreover, many cystinosis patients in poor countries remain undiagnosed and die at a young age due to complications of the disease [24].…”
Section: Overview Of Mutations In the Ctns Gene And Geographical Distmentioning
confidence: 99%
“…In its standard format it involves a breakpoint PCR for the frequent 57 kb deletion followed by sequencing of the coding exons plus neighboring intronic sequence (Topaloglu et al, 2012), an approach which several studies have shown to not reach a 100% mutation detection rate (Shotelersuk et al, 1998;Kalatzis et al, 2002;Mason et al, 2003;Alcantara-Ortigoza et al, 2008;Taranta et al, 2010). As with other genes, many mutations escaping conventional detection strategies can be expected to be large copy number aberrations.…”
Section: Introductionmentioning
confidence: 99%